GPU Assisted Self-Collisions of Cloths - Wojciechowski, Adam; Gałaj, Tomasz (Journal of Applied Computer Science, 2016)
Nowadays, people expectations about high realism in games are very high and computers have to make a huge effort to compute every simple detail that occurs in a virtual 3D scene. Fortunately, we can use power of Graphics Processing Units (GPU) to compute some part of the most computationally heavy algorithms. In this paper, we present method to accelerate computations on GPU using Compute Shaders based on cloth simulation with self-collisions for big number of cloth’s model vertices (more than 2000).